Leadless pacemakers: where is the device?. (24th May 2021) - Elrefai, M; Menexi, C; Roberts, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction Leadless pacemakers (LPs) were designed to avoid lead-related complications associated with transvenous pacing. To minimise the risk of complications, there is preference towards implanting LPs into the septal aspect of the right ventricle rather than the apex or free wall. The Transcatheter Pacing Study (TPS) and the international post-approval registry demonstrated the safety and reliability of the LP systems in real-world settings. The registry demonstrated that more than half of the LPs were implanted into the septum and most required <2 attempts at deployment. We report a radiological method of defining LP position. Methods We reviewed the first 100 LPs implanted at our centre. Two independent observers who didn't implant LPs reviewed the patients' post-implant fluoroscopy images and/or post-implant CXRs when available. The reviewers assessed the devices' positions in postero-anterior (PA) and/or right anterior oblique (RAO) views based on conventional fluoroscopic criteria for lead position. We used the proposed criteria interchangeably on fluoroscopic images and post implant CXRs (Figure). Differences in classification of device position were resolved by consensus. Results Three experienced operators implanted 100 LPs at our centre. Patients (61% male) 56.6 ± 22.2 years had normal hearts (74%), ischaemic cardiomyopathies (12%), congenital heart diseases (6%), valvular pathologies (5%) and dilated cardiomyopathies (3%). Indications for pacing were symptomatic sinus node dysfunction (36%), followed by high grade atrio-ventricular block (33%), bradyarrhythmia associated with atrial tachyarrhythmias (27%) and other indications for pacing (4%). We had a 100% successful implant rate, 88% required ≤2 attempts and 70% required one attempt. There were no major complications. We were able to classify the site of the LPs implants in a total of 90 patients who had fluoroscopic projections or chest x-rays that would allow us to classify the implant sites. A total of 32 implants were in the apex (35.6%). 28 were in mid-septum (31.1 %), 15 in the apical septum (16.7%), 14 on the septal aspect of the right ventricular inflow (15.5%) and 1 implant (1.1%) in the septum of the RV outflow tract. Conclusion: Our proposed method of defining LP position demonstrated that the rate of implants into the true apex at our centre was highly comparable to that of the international registry. It also showed that we had lower rates of implants into the mid-septum in favour of apical septum. There were no pericardial effusions or cardiac perforations resulting from our implant procedures regardless of the site of the implant. We utilised widely used fluoroscopic and chest x-ray criteria for categorisation of the LPs implantation sites. However, a recognised limitation to our analysis is that our findings were not validated using other imaging modalities such as echocardiogram or cardiac computerised tomography (CT).